Penguatan Kapasitas Guru dalam Membangun Sinergi Sekolah dan Orang Tua melalui Parenting Efektif di MIM Jagoan Boyolali - Nisa, Choirun; Prahastiwi, Eka Danik; Hapsari, Rizqa Qodriannisa; Ar-Rif’an, Hanif (Al-DYAS, 2025)
This community service activity aimed to enhance teachers’ capacity in supporting effective parenting at MIM Jagoan Boyolali through training in communication strategies and mentoring skills. The background of this initiative stems from the observed collaboration gap between teachers and parents, which affects the optimal academic and emotional development of students. The method employed consisted of a workshop utilizing lectures, simulations, and group discussions. The results indicated that teachers gained a better understanding of the importance of parenting, effective communication strategies, and their role as mediators between the school and the family. Practical simulations improved teachers’ confidence in engaging with parents, while group discussions created a collaborative space for formulating solutions to various child education challenges. Evaluation of the activity revealed positive responses from participants and led to the initiative of establishing a regular communication forum between teachers and parents. The conclusion of this program is that synergy between schools and families significantly contributes to strengthening support for student development, although limitations in parental involvement and participant reach were noted. The implications suggest that similar programs should be expanded and accompanied by continuous mentoring strategies to optimize teacher–parent collaboration.